Exploring Italianness from the margins: linguistic, generic and cultural hybridisation in contemporary fictions of immigration - Shvanyukova, Polina; Justus Liebig University Giessen (My University, 2014)
The publication of a significant number of linguistically, generically and culturally hybrid Italian novels in the first decade of the twenty-first century has signalled the pressing need for contemporary writers to explore and challenge the dominant notion of Italianness. The novels, that I have decided to designate with the term of ´fictions of immigration´, make part of a larger phenomenon of Italian migration literature, a field that has made significant contributions to the re-definition of the country´s literary and cultural scene in the past twenty years. The defining feature of these more recent hybrid fictions of immigration lies in their attempt to take up the challenge of actively engaging with critical issues that concern contemporary Italian society. These issues comprise first and foremost the questions of (non)belonging for new minority groups in Italy, whose access to symbolic citizenship is denied on the grounds of their incompatibility with the rigid, mainstream construction of Italianness, commonly along the line of colour or a different religious faith. The main goal of this study will be to investigate the ways in which contemporary fictions of immigration actively participate in the critical debate on belonging and the meaning of Italianness in an increasingly hybrid Italian society. More specifically, the focus of the analysis will be on the choice of innovative narrative strategies and hybrid textual features that point to a deeper level of engagement with the complex social issues discussed in the texts in the corpus. Original linguistic features, such as, for example, the use of Italian dialects, will come under scrutiny in the analysis of the linguistic level of the texts, while ruptures with various generic conventions and diversification of the genre spectrum within the genre of Italian fictions of immigration will be systematically explored diachronically, tracing the evolution of the genre since its emergence in the early 1990s to contemporary hybrid fictions of immigration.
Keywords: ddc:800